Manajemen Strategis Kampanye dalam Penanganan Polemik Vaksin Covid 19 - Winda Dwi Astuti Zebua*; Jamiati KN; Lilik Sumarni; Ananda Devina Putri (Universitas Syiah Kuala, 2023)
This article will describe the stages of campaign strategic management in handling the Covid 19 vaccine polemic in Mungka District. The approach used in this article is a qualitative descriptive method. The primary data source used comes from in-depth interviews with three informants and secondary data sources are obtained from documentation and also from various journals from relevant books. The analysis technique in this article is to collect data, examine the collected data, categorize, then test the data, and finally combine all the data by placing the information in chronological order or other order and drawing conclusions. The findings showed that in carrying out the campaign, Mungka District had carried out all the processes of strategic management starting from awareness, formulation, implementation and finally monitoring and evaluating the campaigns that had been carried out. The results of the campaign were stated to be quite effective because they were able to significantly increase the number of people receiving the vaccine.